Safety of Chloroquine or Hydroxychloroquine Plus Azithromycin for the Treatment of COVID-19 Patients in Burkina Faso: An Observational Prospective Cohort Study - Rouamba T; Barry H; Ouédraogo E; Tahita MC; Yaméogo NV; Poda A; Diendéré AE; Ouedraogo AS; Valea I; Koné AM; Thiombiano C; Traoré I; et al. (Dove Medical Press, 2021)
Toussaint Rouamba,1,* Houreratou Barry,2,* Esperance Ouédraogo,1 Marc Christian Tahita,1 Nobila Valentin Yaméogo,3 Armel Poda,4 Arnaud Eric Diendéré,5 Abdoul-Salam Ouedraogo,4 Innocent Valea,1 Amariane M Koné,2 Cherileila Thiombiano,2 Isidore Traoré,2 Zekiba Tarnagda,1 Serge A Sawadogo,6 Zakaria Gansané,7 Yibar Kambiré,8 Idrissa Sanou,8 Fatou Barro-Traoré,8 Maxime K Drabo,1 Halidou Tinto1 On behalf of the CHLORAZ Study Group1Institut de Recherche en Sciences de la Santé (CNRST-IRSS), Nanoro, Burkina Faso; 2Institut National de Santé Publique, Centre Muraz, Bobo-Dioulasso, Burkina Faso; 3Centre Hospitalier Universitaire Yalgado Ouédraogo, Ouagadougou, Burkina Faso; 4Centre Hospitalier Universitaire Sourou Sanon, Bobo-Dioulasso, Burkina Faso; 5Centre Hospitalier Universitaire de Bogodogo, Ouagadougou, Burkina Faso; 6Centre PrïmO Nelson Mandela (Promotion de la Recherche et de l'Innovation en Immunologie Médicale de Ouagadougou), Ouagadougou, Burkina Faso; 7Clinical Monitoring in Africa-Clinical Research Organization, Ouagadougou, Burkina Faso; 8Centre Hospitalier Universitaire de Tengandogo, Ouagadougou, Burkina Faso*These authors contributed equally to this workCorrespondence: Toussaint RouambaInstitut de Recherche en Sciences de la Santé (CNRST-IRSS), 528, Avenue Kumda-Yoore, BP 218 Ouagadougou CMS 11, Ouagadougou, Nanoro, Burkina FasoTel +226 666 532 04Email rouambatoussaint@gmail.comIntroduction: Though chloroquine derivatives are used in the treatment of coronavirus disease 2019 (COVID-19) in many countries worldwide, doubts remain about the safety and efficacy of these drugs, especially in African communities where published data are scarce.Methods: We conducted an observational prospective cohort study from April 24 to September 03, 2020, in Burkina Faso to assess (as primary outcome) the clinical, biological, and cardiac (electrocardiographic) safety of chloroquine or hydroxychloroquine plus azithromycin administered to COVID-19 patients. The main secondary outcomes were all-cause mortality and median time of viral clearance.Results: A total of 153 patients were enrolled and followed for 21 days. Among patients who took at least one dose of chloroquine or hydroxychloroquine (90.1% [138/153]), few clinical adverse events were reported and were mainly rash/pruritus, diarrhea, chest pain, and palpitations. No statistically significant increase in hepatic, renal, and hematological parameters or electrolyte disorders were reported. However, there was a significant increase in the QTc value without exceeding 500ms, especially in those who received chloroquine phosphate. Three adverse events of special interest classified as serious (known from chloroquine derivatives) were recorded namely pruritus, paresthesia, and drowsiness. One case of death occurred. The average onset of SARS-CoV-2 PCR negativity was estimated at 7.0 (95% CI: 5.0- 10.0) days.Conclusion: Hydroxychloroquine appeared to be well tolerated in treated COVID-19 patients in Burkina Faso. In the absence of a robust methodological approach that could generate a high level of scientific evidence, our results could at least contribute to guide health decisions that should be made based on different sources of scientific evidence including those from our study.Keywords: SARS-CoV-2, chloroquine, hydroxychloroquine, azithromycin, safety, virus shedding